Blood-derived amyloid-β protein induces Alzheimer's disease pathologies - Bu, X-L; Xiang, Y; Jin, W-S; Wang, J; Shen, L-L; Huang, Z-L; Zhang, K; Liu, Y-H; Zeng, F; Liu, J-H; Sun, H-L; Zhuang, Z-Q; et al. (Molecular psychiatry, 2018)
The amyloid-β protein (Aβ) protein plays a pivotal role in the pathogenesis of Alzheimer's disease (AD). It is believed that Aβ deposited in the brain originates from the brain tissue itself. However, Aβ is generated in both brain and peripheral tissues. Whether circulating Aβ contributes to brain AD-type pathologies remains largely unknown. In this study, using a model of parabiosis between APPswe/PS1dE9 transgenic AD mice and their wild-type littermates, we observed that the human Aβ originated from transgenic AD model mice entered the circulation and accumulated in the brains of wild-type mice, and formed cerebral amyloid angiopathy and Aβ plaques after a 12-month period of parabiosis. AD-type pathologies related to the Aβ accumulation including tau hyperphosphorylation, neurodegeneration, neuroinflammation and microhemorrhage were found in the brains of the parabiotic wild-type mice. More importantly, hippocampal CA1 long-term potentiation was markedly impaired in parabiotic wild-type mice. To the best of our knowledge, our study is the first to reveal that blood-derived Aβ can enter the brain, form the Aβ-related pathologies and induce functional deficits of neurons. Our study provides novel insight into AD pathogenesis and provides evidence that supports the development of therapies for AD by targeting Aβ metabolism in both the brain and the periphery.